Religious Minorities and Faith-Based Schools in a Quasi-Religious Monopoly - the Difficulties of Inclusion. Issue 2 (3rd April 2019) - Giorda, Maria Chiara; Giorgi, Alberta
Abstract: Italy, which has been defined as a quasi-religious monopoly, is experiencing an increase in religious diversity in the last decades, mainly due to the growing presence of immigration-related religious minorities. As in other countries, in Italy too faith-based as well as secular schools have become a central place for managing religious diversity. In this article, we firstly record on religious diversity in Italian schools and how it is dealt with, showing the primary role of Catholicism in handling religious diversity. Then, we present an overview of Italian faith-based schools, and we focus on how Islam faith- based schools struggle to find a place in the Italian system of education. The results show the quasi-absence of non-Catholic faith-based schools and the strong suspicion against schools based on faiths other than Catholicism. Hence, we argue that actors related to the Catholic Church are in charge of dealing with religious diversity in secular and faith-based schools.